Segmentos anatomocirúrgicos arteriais dos rins de Oryctolagus cuniculus (Linnaeus, 1758) (Lagomorpha — Leporidae) - Moura, Cristiano Rosa de (2003)
The surgical progresses for the nephrosegmentectomy indicate the need of more research to try to identify the anatomicosurgical renal arterial segments of mammals in general, once they supply necessary anatomical bases to the renal surgical interventions, as much as therapeutically as experimentally. In this study, was investigated the anatomicosurgical segments of the kidneys of Oryctolagus cuniculus in what refers to the arterial distribution, whose purpose is to identify, elucidate, to quantify and to denominate such segments. For the accomplishment of this scientiﬁc investigation, 30 pairs of kidneys from rabbits of the Gigantic race (Oryctolagus cuniculus) were used, being 17 males and 13 females, with age from 60 to 90 days, coming from Faval Fanning Equestrian Center LTDA, Três Marias City, Minas Gerais State. The kidneys were removed from each animal, in pairs, united buy their arteries and veins to tracts, respectively, of the abdominal portion of the aorta and caudal vena cava. The renal arteries were dissected and canulated for injection of a vinyl resin colour solution. To follow the respective parts they were submitted to corrosion in an aqueous solution of 30% sulphuric acid for a period of 72 hours in order to obtain the arterial models starting from the ones which, schematic drawings of the distribution of the renal arteries were made, being obtained the following: 1) the right and left renal arteries were always single as for the origin and bifurcated in all of the cases in dorsal and ventral sectorial arteries, and that bifurcation happened at pre- hilar level in all of the cases; 2) the segmented arteries are branches originated from the terminal division of the sectorial arteries, where was found a number from three to seven dorsal and ventral segmented arteries for the right and left kidneys; 3) due to the distribution of the sectorial arteries in the surface of the kidney of rabbits, the existence of two renal sections were veriﬁed such as to the right as for the left, the dorsal and ventral sections, irrigated, respectively, from branches of the dorsal and ventral sectorial arteries; 4) for the right and left kidneys, the dorsal and ventral sectorial arteries are designated to most of the respective surface of the organ, still reaching portions of the opposite arteries, and in some cases are designated exclusively to the respective surface of the organ; 5) for the right kidney, in the dorsal section, a maximum, minimum and medium number was observed, respectively, of 7, 3 and 5.5 anatomicosurgical arterial segments, with larger occurrence of 6; 6) in the ventral section of the right kidney a maximum, minimum and medium number was veriﬁed, respectively, of 7, 3 and 4.9 anatomicosurgical arterial segments, with larger occurrence of 5 segments; 7) a maximum, minimum and medium number, respectively, of 7, 3 and 5.1 anatomicosurgical arterial segments, with larger occurrence of 5, were found in the dorsal and ventral sections of the left kidney; 8) a bilateral symmetry of the anatomicosurgical arterial segment was found in a case (3,3%).